2019
DOI: 10.1177/1368430219839485
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup contact moderates the influence of social norms on prejudice

Abstract: While previous research has examined social norms and intergroup contact as predictors of prejudice, there is limited research on their interplay in shaping intergroup attitudes. The results of five studies using correlational and experimental methods in different intergroup contexts consistently showed that the influence of intolerant (vs. tolerant) social norms on prejudice is reduced for people who have contacts with outgroup members. Studies 4–5 further showed that threat perceptions mediate the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 71 publications
(121 reference statements)
1
19
0
Order By: Relevance
“…Finally, research has also shown that the extent of conformity to ingroup norms is related to individuals’ level of indirect contact. For example, negative ingroup norms increase outgroup prejudice in general, but this effect disappears when an individual's positive interaction with the outgroup is encouraged via imagined contact (Visintin et al., 2019). Indeed, research has shown that anticipating ingroup members having interaction with outgroups predicts interest in cross‐group interaction for both majority and minority groups (Tropp et al., 2014).…”
Section: Mediators Of the Indirect Contact–prejudice Reduction Relatimentioning
confidence: 99%
“…Finally, research has also shown that the extent of conformity to ingroup norms is related to individuals’ level of indirect contact. For example, negative ingroup norms increase outgroup prejudice in general, but this effect disappears when an individual's positive interaction with the outgroup is encouraged via imagined contact (Visintin et al., 2019). Indeed, research has shown that anticipating ingroup members having interaction with outgroups predicts interest in cross‐group interaction for both majority and minority groups (Tropp et al., 2014).…”
Section: Mediators Of the Indirect Contact–prejudice Reduction Relatimentioning
confidence: 99%
“…As developed to explain the central role of the intergroup threats on prejudice, the Integrated Threat Theory (Stephan and Stephan, 2000) has emerged as a theory that has grounded disease-related discrimination research in recent years (e.g., Navarrete and Fessler, 2006;Schaller, 2006;Green et al, 2010Green et al, , 2020Croucher et al, 2020). A considerable amount of research has shown that the perception of the intergroup threat is one of the main antecedents to discrimination (Stephan et al, 2009;Green et al, 2016;Visintin et al, 2020).…”
Section: Implications From Individual Level Theoriesmentioning
confidence: 99%
“…It is common to see individuals in contact as an exception, to evaluate them as a "subtype" and then not to generalize the positive attitude change to aim at the whole group (Stangor, 2009). There are different qualities of contact (contact quantity, contact quality, crossgroup friendships, face-to-face, virtual and parasocial, extended, and imagined) that each have varied effects on intergroup conflicts (Harwood et al, 2013;Visintin et al, 2020). It would therefore be of significant importance to take benefit from the findings of recent extensive research on this subject (e.g., Green et al, 2016Green et al, , 2020Kende et al, 2017;Visintin et al, 2020) in order to determine which type of contact is more appropriate to this process, and how the conditions should be determined.…”
Section: Recommendations For Policymakers and Stakeholdersmentioning
confidence: 99%
See 1 more Smart Citation
“…By extension, intergroup contact might be more effective in countries with fewer LGBT rights. For instance, Visintin, Green, Falomir-Pichastor, and Berent (2020) found that the relation between minority contact and lowered prejudice was stronger in more intolerant or antiegalitarian climates. In other words, the effect of contact was stronger in climates that were more hostile to minority groups, such that having contact with minority group members likely compensated for living in an intolerant climate.…”
Section: Personal Contact 3 Context Interactionsmentioning
confidence: 99%